Emicizumab prophylaxis for people with hemophilia A: Waste estimation and the Brazilian perspective - Ricardo Mesquita Camelo; Mariana Michel Barbosa; Luila Clicia Moura Henriques; Antony Paul Martin; Brian Godman; Augusto Afonso Guerra Júnior; Francisco de Assis Acurcio; Juliana Alvares-Teodoro (Elsevier, 2023)
Costs of hemophilia A treatment are increasing. Waste of clotting products should be avoided. To estimate the first-year waste of emicizumab prophylaxis for people with hemophilia A and inhibitors (PwHAi) who failed immune tolerance induction (ITI), in Brazil. We evaluated the manufacturer and the Brazilian Ministry of Health (MoH) protocol-recommended regimens in a budget impact model. The loading dose consisted of 3.0 mg/kg/Q1W for 4 weeks, for both recommendations. The manufacturer maintenance regimens comprised 1.5 mg/kg/Q1W, 3.0 mg/kg/Q2W, and 6.0 mg/kg/Q4W. The MoH protocol maintenance regimen encompassed a hybrid Q1W/Q2W administration, depending on the body weight. The Q4W regimen was not recommended by the MoH protocol. Analyses were performed to estimate waste given its expense based on the World Health Organization body weight range (percentiles [P] 15, 50, and 85). The first-year emicizumab waste was estimated individually and for the disclosed PwHAi who failed ITI (n = 114). The highest emicizumab waste was estimated for the lowest body weights and the Q1W regimen. The Q4W regimen resulted in the lowest emicizumab waste, followed by the MoH protocol regimen. The total reconstituted costs estimated for the PwHAi who failed ITI according to the hybrid MoH protocol ranged from US$32,858,777 (P15) to US$47,186,858 (P85), with emicizumab waste ranging from 7.9 % (US$2,594,515) to 3.7 % (US$1,738,750), respectively. Lost resources due to current protocols for emicizumab prophylaxis for PwHAi who failed ITI in Brazil are considerable. Waste was more pronounced due to lower body weight and shorter administration intervals.